Peningkatan Hasil Belajar Siswa Pada Pembelajaran Tematik Tema Pertumbuhan dan Perkembangan Makhluk Hidup Memelalui Model Pembelajaran Pendekatan Contextual Teaching and Learning di Kelas III SD Negeri 3 Jebus - Azhar Azhar (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2023)
The purpose of this study was to find out whether there was an increase in student learning outcomes after the application of the Contextual Teaching and Learning Approach. This study used three cycles of action research classroom. Each cycle consists of four stages, namely: design, activities and observations, reflection and revision. The target of this study were Class III students. The data obtained were in the form of end-of-cycle test results, observation sheets of teaching and learning activities. From the results of the analysis, it was found that student learning outcomes had increased from cycle I (57.14%), cycle II (80.95%) , cycle III (90.48%). The average value obtained was 67.10 in cycle I, 78.67 in cycle II, and 84.24 in cycle III. The conclusion of this study is that learning with the Contextual Teaching and Learning Approach can improve the learning outcomes of Grade III students at SD Negeri 3 Jebus and this learning model can be used as an alternative to Thematic learning on the Theme of Growth and Development of Living Things.